Health and Social Relationships : the Good, the Bad, and the Complicated - Newman, Matthew L.; Roberts, Nicole A. (American Psychological Association, 2013)
"Our relationships with other people are complex, but they matter a great deal. In this edited volume, we review recent perspectives on the connections between social relationships and physical and mental health. Although the potential for psychological events and emotions to affect health is no longer novel, our understanding of their intricacies--from physiological processes to cultural mechanisms--is constantly evolving. The individual chapters in this book explore the myriad connections between stress and illness and how these connections are shaped by the quality of our relationships with other people. Relationships, as examined in this volume, span the full continuum--from social support to social isolation--as do their benefits and costs. Throughout the volume, we emphasize two key themes. First, for all the reasons mentioned previously, the chapters emphasize the fact that relationships matter. The quality and quantity of our connections with other people predict outcomes ranging from happiness to heart disease, from adjustment to maladjustment, and from mortality to longevity. The chapters in this volume are designed to explore the scope of and the mechanisms for these associations, as well as their implications for improving both health and relationships. Second, the chapters emphasize the fact that perceptions matter. One of the most robust conclusions from the stress literature (if not all psychological literature) is that people's perceptions are dramatic and important moderators of emotional, behavioral, and physiological responses. Both actual support (e.g., Cohen, 2004) and perceived support (e.g., Lakey & Cassady, 1990) are predictive of better health; both physical isolation (e.g., Berkman & Syme, 1979) and perceived loneliness (e.g., Hawkley et al., 2003) are predictive of poorer health. A host of individual differences likewise moderate the impact of social threat, caregiver stress, romantic loss, and exposure to risky families. Each of the chapters in this volume highlights the importance of perceptions and individual differences and examines the reasons that these play such an important role. The chapters discuss a number of related constructs under the general umbrella of health, including physical and mental health outcomes, as well as the emotional and physiological mechanisms that may act as precursors to these outcomes. In many cases, these chapters examine moderators of the link between health and relationships--for example, the impact of a romantic loss depends in part on the personality and gender of the person experiencing the loss. In other cases, where the mechanisms are understood, the chapters focus on mediators of the link between health and relationships--for example, physical affection appears to be the mediating mechanism for the health benefits of marriage. The topic of health and social relationships spans multiple perspectives within psychology and related fields, and we have attempted to capture this diversity in this volume. Although the primary intended audience is academic psychologists, we believe that many of the chapters will be of interest to health care professionals and therapists who focus on relationship issues. We also anticipate this volume can be an excellent companion to graduate and advanced undergraduate courses on the topics of stress, health, emotion, and relationships"--Introduction. (PsycINFO Database Record (c) 2012 APA, all rights reserved).